Coordination complex [Eu(μ2-OC2H5)(btfa)(NO3) (phen)]2·phen with high luminescent efficiency - Iovu Mihail (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2021)
Experimental results on the bis[(μ2-etoxi)(benzoyl trifluoroacetonato)(nitrato)(1,10-phenantroline)europium(III)]1,10-phenantroline europium(III) coordination complex (hereafter, [Eu(μ2-OC2H5)(btfa)(NO3)(phen)]2·phen) are described. The complex is characterized by photoluminescence (PL) and infrared spectroscopy. Photoluminescence spectra of the complex exhibit strong emission with specific narrow emission bands associated with the 5D0→7Fj (j = 0–4) transitions. The pattern of emission band splitting and the luminescence time decay suggest the presence of at least two different sites of the Eu3+ ion in a low-symmetry environment. The absolute PL quantum yield of the complex is determined to be 49.2%.Sunt prezentate rezultate experimentale pentru complexul coordinativ al europiului III) - [Eu(μ2-OC2H5)(btfa)(NO3)(phen)]2phen. Complexul a fost caracterizat prin spectroscopia de fotoluminescență și spectroscopia în infraroșu. Spectrele de fotoluminescență ale complexului reprezintă benzi de emisie puternice asociate cu tranzițiile 5D0→7Fj (j=0-4). Caracterul despicării benzilor de emisie, cât şi timpul de relaxare al luminescenței indică prezența a cel puțin două site-uri diferite ale ionului Eu3+ în mediu cu simetrie redusă. A fost determinat randamentul cuantic absolut al complexului de 49,2%.